2012
DOI: 10.3109/08037051.2012.680742
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and antihypertensive treatment in HIV-infected individuals. A longitudinal cohort study

Abstract: HIV duration predicted new-onset hypertension, which could suggest involvement of low-grade inflammation; this hypothesis needs to be further explored. Despite increased use of antihypertensive treatment, enhanced awareness and adequate treatment of hypertension are still warranted in HIV-infected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 163 publications
0
19
2
1
Order By: Relevance
“…In this prospective, longitudinal study on BP, 542 patients attending the outpatient clinic at the Department of Infectious Diseases at Oslo University Hospital, Ullevål, finished the baseline study and 434 HIV‐infected patients (80%) completed the follow‐up study, as detailed previously 36 . Of the 108 patients lost to follow‐up, more were normotensive compared with those who completed the study (80.6% vs 65.2%, P =.002).…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…In this prospective, longitudinal study on BP, 542 patients attending the outpatient clinic at the Department of Infectious Diseases at Oslo University Hospital, Ullevål, finished the baseline study and 434 HIV‐infected patients (80%) completed the follow‐up study, as detailed previously 36 . Of the 108 patients lost to follow‐up, more were normotensive compared with those who completed the study (80.6% vs 65.2%, P =.002).…”
Section: Methodsmentioning
confidence: 88%
“…Sustained hypertension was characterized as persistent hypertension both at baseline and at follow‐up. Because considerable dynamics in the hypertension status has been found in this population, 36 sustained hypertension was chosen as the main focus in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The rates we detected in this cohort appear similar to or higher than that of prior estimates among HIV positive populations in resource-rich settings. [26-28] For example, we estimated an overall incidence of hypertension of 111.5 per 1000 py (95% CI 101.9 - 121.7), which is higher in magnitude than estimates described among PLWH in Norway (29.8 per 1000 py, 95% CI 20.3–42.2),[28] a multi-center study in the United States (64.1 per 1000 py, 95% CI 58.7 - 69.9)[26], and from the D:A:D study cohort which enrolls participants from sites in Europe, the United States, and Australia (72.1/1000py, 95%CI 68.2 – 76.0). Although we cannot make direct comparisons from study to study, our data offer preliminary evidence of higher rates in our patient population than those from resource rich settings.…”
Section: Discussionmentioning
confidence: 99%
“…For hypertension specifically, studies have found both an increased risk of hypertension for those with HIV [11, 12], and an association between hypertension with elements of the metabolic syndrome, including insulin resistance and lipodystrophy [13, 14]. Similar, to other cardiovascular diseases, the risk of hypertension among those with HIV has been associated with duration of HIV infection [15, 16], as well as traditional risk factors [17, 18], suggesting that HIV infection might have independent effects. The data on the associations between ART and hypertension is inconclusive, with some studies noting increased risk with ART exposure [19], while others not [17, 20].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis, including 49 studies with 63,554 participants from America, Europe, Africa and Asia from 1996 to 2014, reported an estimated hypertension prevalence of 12.7% for ART-naïve and 34.7% for ART-experienced participants (3). Epidemiological studies from the United States and several European countries have demonstrated incidence of hypertension among outpatient primary care and HIV clinics for PLWH ranging from 2.6 to 7.2 per 100 person-years (PYs) (4)(5)(6)(7)(8)(9). Studies from East Africa have reported incidence rates of 11.2-12.0 per 100 PYs (10,11).…”
Section: Introductionmentioning
confidence: 99%